2015
DOI: 10.1158/2326-6066.cir-15-0062
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Role of Invariant NKT Cells in Tumor Immunity

Abstract: Invariant natural killer T (iNKT) cells are a unique population of T lymphocytes, which lie at the interface between the innate and adaptive immune systems, and are important mediators of immune responses and tumor surveillance. iNKT cells recognize lipid antigens in a CD1d-dependent manner; their subsequent activation results in a rapid and specific downstream response, which enhances both innate and adaptive immunity. The capacity of iNKT cells to modify the immune microenvironment influences the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 160 publications
0
107
0
Order By: Relevance
“…Indeed, during immunosurveillance, iNKTs can recognize endogenous lipids presented by CD1d molecules on tumors cells and subsequently eliminate tumor cells directly through iNKT-mediated lysis. 8 Thus, iNKTs have been shown to be protective in the antitumor immune response to B-cell lymphoma in a CD1d-dependent manner. 30 Of note, CD1d is preferentially expressed in hematopoietic cells, 31 and hematologic malignancies retain this expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, during immunosurveillance, iNKTs can recognize endogenous lipids presented by CD1d molecules on tumors cells and subsequently eliminate tumor cells directly through iNKT-mediated lysis. 8 Thus, iNKTs have been shown to be protective in the antitumor immune response to B-cell lymphoma in a CD1d-dependent manner. 30 Of note, CD1d is preferentially expressed in hematopoietic cells, 31 and hematologic malignancies retain this expression.…”
Section: Discussionmentioning
confidence: 99%
“…5 Chaidos et al focused on invariant natural killer T cells (iNKTs), 6 a regulatory cell population implicated in immune tolerance and tumor surveillance. 7,8 They reported that the use of PBSC graft with fewer CD4 2 iNKTs was associated with an increased risk of acute GVHD (aGVHD). 6 Similarly, Rezvani et al evaluated regulatory T cells (Tregs) within the PBSC graft 9 and reported that patients who received allo-SCT with a PBSC graft that contained lower absolute number of Tregs were associated with a greater risk of developing aGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…The potential importance of NKTs for tumor immunity and immunotherapy has been demonstrated in multiple models of cancer in mice and in early-stage clinical trials in cancer patients (5)(6)(7)(8)(9)(10). In contrast to T cells, NKTs effectively traffic to the tumor site and can mediate antitumor responses via either direct killing of CD1d + tumor cells, inhibition of tumor-supportive macrophages, or transactivation of NK cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their critical regulatory roles in immunity, class Ib and interacting iT cells such as iNKT and MAIT cells have emerged as suitable therapeutic targets against viral, microbial, and parasitic infections, autoimmune and allergic diseases, as well as malignant neoplastic growths (Fernandez et al, 2014; Juno et al, 2012; Macho-Fernandez and Brigl, 2015; McEwen-Smith et al, 2015; Robertson et al, 2014; Skold and Behar, 2003; Subleski et al, 2011). However, the clinical implementation of class Ib- and iT cell-based therapies is still far from realization and requires a deeper and more comprehensive understanding of the biology of this a system.…”
Section: Introductionmentioning
confidence: 99%